2021
DOI: 10.1016/j.msec.2020.111745
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic and antibacterial surfaces on additively manufactured porous Ti-6Al-4V implants: Combining silver nanoparticles with hydrothermally synthesized HA nanocrystals

Abstract: The recently developed additively manufacturing techniques have enabled the fabrication of porous biomaterials that mimic the characteristics of the native bone, thereby avoiding stress shielding and facilitating bony ingrowth. However, aseptic loosening and bacterial infection, as the leading causes of implant failure, need to be further addressed through surface biofunctionalization. Here, we used a combination of (1) plasma electrolytic oxidation (PEO) using Ca-, P-, and silver nanoparticle-rich electrolyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…Figure 3A illustrates the grazing incidence X-ray diffraction patterns of the u Ti-6Al-4V ELI alloy and the PEO coatings produced at different electrical param The three samples had formed coatings that were extremely well attached to the AM substrate composed of two different layers, one dense inner layer, and a porous outer layer, as seen in Figure 1. This result agrees with those found by Fazel et al [29] in their work on PEO coatings obtained on Ti-6Al-4V alloy processed by the L-PBF technique. The inner layer, which grows direct into the metal under high pressures and temperatures, is dense, crystalline, and firmly attached to the substrate.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Figure 3A illustrates the grazing incidence X-ray diffraction patterns of the u Ti-6Al-4V ELI alloy and the PEO coatings produced at different electrical param The three samples had formed coatings that were extremely well attached to the AM substrate composed of two different layers, one dense inner layer, and a porous outer layer, as seen in Figure 1. This result agrees with those found by Fazel et al [29] in their work on PEO coatings obtained on Ti-6Al-4V alloy processed by the L-PBF technique. The inner layer, which grows direct into the metal under high pressures and temperatures, is dense, crystalline, and firmly attached to the substrate.…”
Section: Resultssupporting
confidence: 93%
“…Yu and Choe [28] demonstrate that PEO coatings composed of Ca/P and TiO 2 , formed on Ti-6Al-4V substrate, were capable to induce the formation of hydroxyapatite (HA) by immersion in SBF, which exhibits superior bioactivity when compared with the naked substrate [21]. The biological response of PEO coatings, combined with a hydrothermal layer of HA, obtained on Ti-6Al-4V substrate produced by additive manufacture techniques, was evaluated by Fazel et al [29]. According to the authors, the coatings showed a biological response facilitating the proliferation and osteogenic differentiation of cells.…”
Section: Introductionmentioning
confidence: 99%
“…Silver and hydroxyapatite are two typical materials with antibacterial and osteogenic properties, respectively. Recently, Fazel et al developed a duplex process that sequentially employed micro-arc oxidation and hydrothermal treatment to decorate Ag NPs and hydroxyapatite nanocrystals on the surface of a porous Ti6Al4V substrate (fabricated by using selective laser melting), creating surfaces of both osteogenic and antibacterial properties [ 206 ]. Bacterial infection in burn wounds is common and fatal [ 207 ].…”
Section: Innovative Designs To Mitigate Device-associated Infectionsmentioning
confidence: 99%
“…The AgNP-based composites have been combined with natural and synthetic polymeric substances for tissue engineering applications [27,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. Biocomposites containing AgNPs and HA have been produced using ecofriendly techniques [68].…”
Section: Preparation Of Ha-agnp Biocompositesmentioning
confidence: 99%